1980
DOI: 10.1002/crat.19800150315
|View full text |Cite
|
Sign up to set email alerts
|

The polymorphism of some liquid crystalline 4′‐n‐alkyloxy‐3′‐nitro‐biphenylcarboxylic acids

Abstract: The substances of the homologous series with n = 6, 12, 14, 15, 16, 18 were investigatec .y calorimetry and microscopy. I n the lower nienibers exist nematic, smectic A and smectic C phases, in the homologs with lz = 16 and 18 appear phases of the type smectic D with cubic structure. The kinetics of these phase transitions, in which smectic D is participating shows a strong dependence upon the experimental conditions. Supercooling, as well as, overheating effects were found. I n the supercooled state we could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 8 publications
1
40
0
Order By: Relevance
“…The spectral pattern of the SmA phase changed with time after the temperature was equilibtemperature does not correspond well to the temperature at which the T1± 1/T curve bends, but we ascribe this rated, suggesting a tendency for change of the molecular orientation under the magnetic ® eld. The ® nal signal in small discrepancy to the di culty of determining the I1± I2 transition temperature exactly because of the very ® gure 1 shows a doublet pattern with a quadrupole splitting (DnQ) of 7´0 kHz, indicating a uni-axial property broad nature of this transition in DSC [3,4 ]. The plots for ANBC-14 consisted of three regions, corresponding of spin one (I=1) nuclei [11,15].…”
Section: Ex Perimentalmentioning
confidence: 93%
See 1 more Smart Citation
“…The spectral pattern of the SmA phase changed with time after the temperature was equilibtemperature does not correspond well to the temperature at which the T1± 1/T curve bends, but we ascribe this rated, suggesting a tendency for change of the molecular orientation under the magnetic ® eld. The ® nal signal in small discrepancy to the di culty of determining the I1± I2 transition temperature exactly because of the very ® gure 1 shows a doublet pattern with a quadrupole splitting (DnQ) of 7´0 kHz, indicating a uni-axial property broad nature of this transition in DSC [3,4 ]. The plots for ANBC-14 consisted of three regions, corresponding of spin one (I=1) nuclei [11,15].…”
Section: Ex Perimentalmentioning
confidence: 93%
“…compounds exhibiting an optically isotropic D phase, Ukleja et al [9 ] measured relaxation times and di usion and thus have attracted the scienti® c interest of many constants for ANBC-16 using solid state 1 H NMR researchers. The D phase was ® rst discovered in two spectroscopy and showed that in the D phase the members, ANBC-16 and -18 by Gray et al [1 ], and molecular motions are isotropic on the time scale of characterized by Demus et al [2,3 ]. Recently, we NMR, and di usional motions of the molecules are not found that the D phase exists as a thermally stable and ® xed to one unit cell of the cubic lattice.…”
Section: Introductionmentioning
confidence: 99%
“…Deviation of the results in different regions of the same melting curve indicates that several solid modifications exist, making a reliable purity determination nearly impossible. connected with liquid crystals occur much faster, but in some cases strong hindrances could be observed, as in transitions into solid phases [12]. In the isothermal method, which is well adapted to the Avrami equation, calorimetric curves at constant supercooling or overheating are plotted vs. time.…”
Section: Special Investigationsmentioning
confidence: 99%
“…4 0 -n-alkoxy-3 0 -nitrobiphenyl-4-carboxylic acids (designated as ANBC-n, where n is the number of carbon atoms in the alkoxy groups) are well known for exhibiting thermotropic cubic (Cub) phases [1][2][3][4][5][6][7][8][9][10][11][12][13][14], and two lattice types (Ia3d and Im3m) have been reported, the formation of which is strongly dependent on the alkoxy chain length n. When 15 n 18, the Ia3d-Cub phase is formed, and for 19 n 21, the Im3m type is seen, both on heating and cooling (except for n ¼ 15, where the Cub phase is observed only on the first heating of the virgin sample) [12][13][14]. Since one cubic lattice contains more than one thousand molecules, and thus, it is very difficult to deduce the packing at the molecular level from the lattice dimension and the packing symmetry obtained.…”
Section: Introductionmentioning
confidence: 99%